2021
DOI: 10.3389/fpsyg.2021.582421
|View full text |Cite
|
Sign up to set email alerts
|

How I See Me—A Meta-Analysis Investigating the Association Between Identities and Pro-environmental Behaviour

Abstract: Prolific research suggests identity associates with pro-environmental behaviours (PEBs) that are individual and/or group focused. Individual PEB is personally driven, self-reliant, and are conducted on one's own (e.g., home recycling). Group focused PEB is other people-reliant and completed as part of a group (e.g., attending meetings of an environmental organisation). A wide range of identities have been related to PEBs. For example, a recent systematic qualitative review revealed 99 different types of identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 170 publications
(228 reference statements)
3
22
1
2
Order By: Relevance
“…The relation between habit and self-identity may stem from habits being based on important values, which can be considered as long-term motivations. This may pertain to personal identities but equally to shared social identities (Udall et al 2021). Verplanken and Sui (2019, Study 2) provided experimental evidence that the association of habits with self-identity is stronger if habits are linked to values.…”
Section: The Role Of Rewardsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relation between habit and self-identity may stem from habits being based on important values, which can be considered as long-term motivations. This may pertain to personal identities but equally to shared social identities (Udall et al 2021). Verplanken and Sui (2019, Study 2) provided experimental evidence that the association of habits with self-identity is stronger if habits are linked to values.…”
Section: The Role Of Rewardsmentioning
confidence: 99%
“…Slovinec D'Angelo et al (2014) monitored physical exercise among coronary heart disease patients and found that self-efficacy and autonomous motivation were predictors in the short-term (6 months), while autonomous motivation continued to predict engagement in physical exercise in the longer term (12 months). A long-term habit may become 'mine' or part of my identity and may thus implicate the self (Udall et al 2021). Verplanken and Sui (2019, Study 1) showed that the degree to which participants associated habits with their true self correlated with selfintegration, self-esteem and an orientation towards an ideal self.…”
Section: The Longevity Of Habitual Behaviormentioning
confidence: 99%
“…Therefore, environmental decisions are not just choices of personal lifestyle; they are more related to moral action [ 3 , 4 ]. Pro-environmental behavior (PEB), which consists of recycling water, paper and clothes, conserving energy, taking public transportation, green consumption, eating more fruits and vegetables, and donating to environmental campaigns or charities, is motivated by moral emotions [ 5 , 6 , 7 ]. Therefore, engaging in sustainable activities facilitate individuals to leave or maintain a good impression and seek high social status [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that social comparisons motivate consumption, including seeking status, showing off personal distinction, and “keeping up with joneses” [ 17 ]. As a result, it might contribute to irrational consequences such as overconsumption, resource wasting, and environmental damage [ 5 ] Envy occurs in the upward social comparisons when similar people acquire something (e.g., ideal quality, opportunity, task performance and product) that individuals are longing for [ 18 , 19 ]. It is not only defined as a state driven by situations but also conceptualized as a personality trait—dispositional envy that describes the chronic feeling of envy in social settings [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, because observational data on individual PEBs are difficult to obtain, we relied on the literature and used a self-report method to measure public tendency and intent to engage in waste separation and other PEBs. However, to a certain extent, the type of behavioral measurement and research settings altered the associations between identity and PEBs [ 93 ]. Therefore, the methodological limitations may have affected the external validity of our results.…”
Section: Discussionmentioning
confidence: 99%